Effects of maternal stress on Reelin signaling and migration of GABAergic interneurons in the prefrontal cortex of postnatal rats - Kolaka, Ratirat; Vanichviriyakit, Rapeepun; Chutabhakdikul, Nuanchan (Journal of Medicine and Health Sciences, 2021)
Stress during pregnancy affects fetal brain development and increases the risk of subsequent neuropsychiatric diseases. The prefrontal cortex (PFC) plays important role in higher cognition and its impairment is associated with neuropsychiatric disorders. GABAergic interneurons are the last group of neurons that migrate into the cortex and plays a crucial role in modulating cortical output for proper sensory gating function and cognition. Reelin is an extracellular matrix protein that plays role in neural migration and its dysfunction causes the abnormal positioning of neurons in the cortex. Importantly, both the dysfunction of reelin and the abnormal function of GABAergic interneurons are associated with the pathology of neuropsychiatric disorders. However, it is still not clear how maternal stress alters GABAergic interneurons migration in the brains of the rat pups. The present study investigates the effect of MS on reelin signaling and the migration of GABAergic interneurons in the PFC among the rat pups. The pregnant rats were divided into two groups; maternal stress (MS) and the control group. The distribution of GABAergic interneurons and the expression level signaling proteins for the reelin pathway were measured and compared between groups. at a statistically significant level of 0.05. The results revealed that MS significantly decreased GABA-immunopositive cells in the PFC of rat pups as compared to the control. Besides, MS temporarily increases reelin expression in the PFC of newborn pups, but later decreased at postnatal day (P)7. In addition, MS-induced a significant decrease in VLDLR and Dab1 expression in the PFC of rat pups at P7-P14. Altogether, the results indicated that MS has long-term effects on GABAergic interneurons migration in the prefrontal cortex of rat pups and the mechanism might be related to the dysfunction of reelin signaling. In conclusion, reelin dysfunction and abnormal positioning of GABAergic interneurons might be the mechanism that links early-life stress and the emergence of neuropsychiatric disorders later in life.